The 23S Ribosomal RNA From Pyrococcus furiosus Is Circularly Permuted - Ulf Birkedal; Bertrand Beckert; Daniel N. Wilson; Henrik Nielsen; Henrik Nielsen (Frontiers in Microbiology, 2020)
Synthesis and assembly of ribosomal components are fundamental cellular processes and generally well-conserved within the main groups of organisms. Yet, provocative variations to the general schemes exist. We have discovered an unusual processing pathway of pre-rRNA in extreme thermophilic archaea exemplified by Pyrococcus furiosus. The large subunit (LSU) rRNA is produced as a circularly permuted form through circularization followed by excision of Helix 98. As a consequence, the terminal domain VII that comprise the binding site for the signal recognition particle is appended to the 5´ end of the LSU rRNA that instead terminates in Domain VI carrying the Sarcin-Ricin Loop, the primary interaction site with the translational GTPases. To our knowledge, this is the first example of a true post-transcriptional circular permutation of a main functional molecule and the first example of rRNA fragmentation in archaea.